ANALISA DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI KEPEGAWAIAN DIREKTORAT JENDERAL PENGEMBANGAN EKSPOR NASIONAL KEMENTERIAN PERDAGANGAN R.I. - Hendri Irawan; Yudho Waskito (Universitas Budi Luhur, 2011)
Personnel Management is an essential part in managing the organization effectively, currently, almost all public or private enterprises, organizations and institutions are already using personnel administration system which is served for managerial and technical operation. Recently in serving the personnel administrative process of Director General of National Export Development, Indonesian Ministry of Trade, they already use microsoft Office. By using these system for presenting Information, they feel that the system is not optimal. Therefore, they design a computerized system by using object oriented method, in processing administration for reducing shortages of the running system in order to improve the information quality produced. Keyword : Information Systems, Personel Administration